Structural Safety Assessment of Exploited Buildings - Madgoziev Khusan Melibaevich,; Gulhayo Manasurova,; Tursunzoda Jasmina, (European Journal of Life Safety and Stability (2660-9630), 2022)
Ensuring the structural safety of buildings is only possible through an accident risk management system at all stages of the life cycle. Therefore, the development of methods that allow determining the risk of an accident in operated buildings and assessing their residual life by the magnitude of this risk is an urgent task and an urgent need for the construction complex of the Republic of Uzbekistan. The theoretical and methodological basis of the research is a systematic approach with the use of comparative analysis and comparison, methods of probability theory, fuzzy set theory and fuzzy logic techniques, methods of structural mechanics and methods of structural analysis.